A STUDY ON IMPACT OF HUMAN RESOURCE ACCOUNTING IN EDUCATIONAL INSTITUTIONS – WITHSPECIAL REFERENCE TO BANGALORE CITY COLLEGES - Ingrid, Merlin; Amaladas, L. Augustin (European Scientific Journal, ESJ, 2014)
From a decade most of the corporate have started accounting the value of the employees using varies approaches. The reason being, the value and importance of Human Resource which is considered as the most successful resource of an organization is recognized and identified. Human resources accounting is the process of identifying and reporting the investment made in the human resources of an organization to the interested parties. The main concept behind Human Resources Accounting is the investment made on each employee and the value generated by them. In this context, it is immense difficult to account the resources of institutions in which profits and productivity heavily depends on intangible assets. This attempt becomes much difficult in the case of knowledge carriers and intellectuals. Intellectual capital has become an accounting component since a decade. Here is an attempt to quantify the investment made in intellectual and knowledge resources and obtain their future value. This paper aims at studying the concept behind quantifying and accounting for Human Assets in academic institution that help in the development of the institution and society. For this study, four colleges namely St. Josephs College of commerce, JyotiNivas College, Krupanidhi College and Vijaya College have been studied. A questionnaire was used to obtain the opinion of the employees and management in this concept. On the analysis of the data it was discovered that most of the employees and management feel that Human Resource Accounting in academics should be introduced. Here Chi square test, a statistical tool, is used to prove hypothesis. The test proves that HRA will create a positive impact on the teaching faculties. There will be a significant impact on the productivity of the teachers and goodwill of the institution. In other words, introduction of Human Resource Accounting will increase the efficiency of the teachers and goodwill of the institution.